Managing and Mining Web Multimedia – B-Tree Indexing Approach - Siddu P, Algur; Basavaraj A, Goudannavar (International Journal of Computer Sciences and Engineering, 2025)
Develop a proper method in multimedia data management is important to support multimedia application’s domain. Multimedia is defined as the combination of more than one media; they may be of two types - static and dynamic media. Text, graphics, and images are categorized as static media; on the other hand, objects like- animation, music, audio, speech, video are categorized as dynamic media. To manage this multimedia database management system is essential. Multimedia database management system can be defined as software system that manages a collection of multimedia data. Generally, multimedia database contains text, image, animation, video, audio, movie sound etc. But, all data are stored in the database in binary form. The paper presents the effective framework for the multimedia database management in terms of B-tree indexing. The framework is to ensure that the process of data manipulation, store, in a distributed environment can be conducted in an efficient manner.